The world crisis and Latin America.: Conclusions of the meeting of leading personalities convened by ECLA in Bogotá from 19 to 21 May 1983 - United Nations (CEPAL Review, 1983)
The Executive Secretary of ECLA called together a group of leading Latin American personalities* in order to analyse, on a strictly personal basis and without implying that their views were shared by their respective governments or institutions, the impact of the international economic crisis on Latin America and possible solutions to this problem. The meeting took place in Bogotá from 19 to 21 May 1983 and was officially opened by the President of Colombia, Dr. Belisario Betancur.